Pilot testing the EARS-Vet surveillance network for antibiotic resistance in bacterial pathogens from animals in the EU/EEA - Lagrange, Justine; Amat, Jean-Philippe; Ballesteros, Cristina; Damborg, Peter; Grönthal, Thomas; Haenni, Marisa; Jouy, Eric; Kaspar, Heike; Kenny, Kevin; Klein, Babette; Lupo, Agnese; Madec, Jean-Yves; et al. (Frontiers in Microbiology, 2023)
As part of the EU Joint Action on Antimicrobial Resistance (AMR) and Healthcare-Associated Infections, an initiative has been launched to build the European AMR Surveillance network in veterinary medicine (EARS-Vet). So far, activities included mapping national systems for AMR surveillance in animal bacterial pathogens, and defining the EARS-Vet objectives, scope and standards. Drawing on these milestones, this study aimed to pilot test EARS-Vet surveillance, namely to i) assess available data, ii) perform cross-country analyses, and iii) identify potential challenges and develop recommendations to improve future data collection and analysis. Eleven partners from nine EU/EEA countries participated and shared available data for the period 2016 – 2020, representing a total of 140,110 bacterial isolates and 1,302,389 entries (isolate-antibiotic agent combinations). Collected data were highly diverse and fragmented. Using a standardized approach and interpretation with epidemiological cut-offs, we were able to jointly analyse AMR trends of 53 combinations of animal host-bacteria-antibiotic categories of interest to EARS-Vet. This work demonstrated substantial variations of resistance levels, both among and within countries (e.g., between animal host species). Key issues at this stage include the lack of harmonization of antimicrobial susceptibility testing methods used in European surveillance systems and veterinary diagnostic laboratories, the absence of interpretation criteria for many bacteria–antibiotic combinations of interest, and the lack of data from a lot of EU/EEA countries where little or even surveillance currently exists. Still, this pilot study provides a proof-of-concept of what EARS-Vet can achieve. Results form an important basis to shape future systematic data collection and analysis.